Pengembangan Sistem Informasi E-Commerce dengan Pemanfaatan API Midtrans menggunakan Framework Laravel (Studi Kasus : Byboot.id) - Muhamad Maulana Zuhad Aditya; Widhy Hayuhardhika Nugraha Putra; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Byboot.id is a women's shoe store located in Jombang, East Java. Byboot.id has an online store that has been around since 2018, where the product catalog can be seen on Instagram @byboot_official. Ordering at this store online can only be done via messages on Instagram or WhatsApp. There are problems for ordering online, namely only accepting payments via bank transfer and verification that is still done manually. So that the payment process to verification takes a relatively long time. This problem in ordering and paying has made Byboot.id lose customers. In this research, a website has been created that can overcome the problems that occur in Byboot.id. In payment problems, a payment gateway service is used, namely Midtrans which can provide an automatic payment system. From this study, the results of functional testing using the blackbox method with validation tests were carried out on all system functions and obtained 100% valid results. The results of non-functional testing of the system using compatibility testing show that the website can run on various browsers. As for the results of the User Acceptance Testing (UAT) test, it was obtained a score of 80.5% with a good category.